Pentingnya Partisipasi Publik dalam Perencanaan Pembangunan Nasional - Oeleu, Frederika; Betzy Cleodiva Moyna Djawa; Petrus Alexandro Kelen; Alfa Marthin Radja; Gabriel Erik Naijes; Adelheid Elisabet Loda; Joaquina Felicia Saru (Lembaga Pengembangan Kinerja Dosen, 2026)
Public participation is recognized as an essential principle in national development planning; however, its implementation in the Musrenbang process remains largely formal, government-dominated, and lacks transparency. This qualitative case study research analyzes the influence of public participation on the quality of planning, as well as the factors that hinder or support it, through interviews, observations, and document analysis. The results show that participation is at the tokenism level and is not yet inclusive, including in the utilization of e-Musrenbang. The study highlights the need for strengthening transparency, access to information, and community empowerment to achieve meaningful participation and more inclusive development. It emphasizes that public involvement is still symbolic rather than impactful, particularly for marginalized groups. Therefore, the study calls for enhancing the effectiveness of e-Musrenbang and creating a more inclusive space for community participation. By doing so, Musrenbang can become a more empowering platform that enables broader community engagement and contributes to fairer, more sustainable development.